BrCPS1 Function in Leafy Head Formation Was Verified by Two Allelic Mutations in Chinese Cabbage (Brassica rapa L. ssp. pekinensis) - Gao, Yue; Qu, Gaoyang; Huang, Shengnan; Liu, Zhiyong; Fu, Wei; Zhang, Meidi; Feng, Hui (Frontiers in Plant Science, 2022)
The formation of the leafy heads of Chinese cabbage is an important agricultural factor because it directly affects yield. In this study, we identified two allelic non-heading mutants, nhm4-1 and nhm4-2, from an ethyl methanesulfonate mutagenic population of a heading Chinese cabbage double haploid line “FT.” Using MutMap, Kompetitive Allele-Specific PCR genotyping, and map-based cloning, we found that BraA09g001440.3C was the causal gene for the mutants. BraA09g001440.3C encodes an ent-copalyl diphosphate synthase 1 involved in gibberellin biosynthesis. A single non-synonymous SNP in the seventh and fourth exons of BraA09g001440.3C was responsible for the nhm4-1 and nhm4-2 mutant phenotypes, respectively. Compared with the wild-type “FT,” the gibberellin content in the mutant leaves was significantly reduced. Both mutants showed a tendency to form leafy heads after exogenous GA3 treatment. The two non-heading mutants and the work presented herein demonstrate that gibberellin is related to leafy head formation in Chinese cabbage.